2020
DOI: 10.1111/pim.12715
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential protein recognition pattern between Naegleria fowleri and Naegleria lovaniensis

Abstract: Many pathogenicity factors are involved in the development of primary amoebic meningoencephalitis (PAM) caused by N fowleri. However, most of them are not exclusive for N fowleri and they have not even been described in other nonpathogenic Naegleria species. Therefore, the objective of this work was to identify differential proteins and protein pattern recognition between Naegleria fowleri and Naegleria lovaniensis using antibodies anti‐N fowleri as strategy to find vaccine candidates against meningoencephalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…As we mentioned above, in a recently published work [11], we found differential proteins between N. fowleri and N. lovaniensis, specifically using IgG antibodies by 2-DE Western blot assay. However, the analysis did not include an immunization scheme, with or without CT as an adjuvant, in order to assess survival rates with different numbers of immunizations.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…As we mentioned above, in a recently published work [11], we found differential proteins between N. fowleri and N. lovaniensis, specifically using IgG antibodies by 2-DE Western blot assay. However, the analysis did not include an immunization scheme, with or without CT as an adjuvant, in order to assess survival rates with different numbers of immunizations.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, many immunogenic bands, including these six bands, were adjuvanted by CT, where some proteins were identified, such as myosin II heavy chain (Q25561), actin (B5M6J9), ATP synthase F1 subunit alpha (M4H5H9), amino acid decarboxylase (C6L6E3), membrane protein (Q95UJ2), Hsp70 (Q6B3P1), and glyceraldehyde 3 phosphate dehydrogenase (D2W142). These are proteins that had been previously reported by Gutiérrez-Sanchez et al (2020) [11], with differential expression between N. fowleri and N. lovaniensis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The results obtained showed very notable differences in spot intensity between these two species by 2-DE gels and 2-DE Western blot, specifically those with relative molecular weights of 100, 75, 50 and 19 kDa. Some spots corresponding to these molecular weights were identified as actin fragment, myosin II, heat shock protein, and membrane protein Mp2CL5, among others, with differences in theoretical post-translational modifications [ 34 ]. Interestingly, it has been shown that some pathogenicity factors are not exclusive to N fowleri , since they have also been reported in nonpathogenic Naegleria species with different levels of expression [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study has revealed a membrane protein called Mp2CL5 (17 kDa) in pathogenic Naegleria species. It has been proposed that it plays a role in the amoeba’s cellular recognition and adhesion [ 37 ].…”
Section: Pathogenesis Of Pammentioning
confidence: 99%